The 2008 Global Financial Crisis and COVID-19 Downturn: Parallels and Lessons - Lisa Jerde Spillman; James Ondracek; Mohammed Saeed; Karli Peterson; Andy Bertsch (International Journal of Organizational Business Excellence, 2023)
The Global Financial Crisis of 2008 (GFC) and the COVID-19 downturn wreaked havoc on the global economy and people across the world. Lessons learned from the GFC can help the country and the world rebound from COVID-19. The research addresses the causes of the GFC and how it unfolded in the United States (US). It also discusses how the crisis spread from the US to the United Kingdom (UK) and China, as well as rescue efforts in those countries and the role of the International Monetary Fund (IMF). In addition, the research discusses the COVID-19 downturn, the parallels, and differences between the GFC and the downturn, and the lessons of the GFC that can be applied to the COVID-19 downturn. Finally, the research recommends a strategic financial rescue plan to restart post COVID-19 economic growth in the US.